The Lived Experiences of Mentoring Nurses in Malaysia - Enrico, Noraini Binti (Nurse Media Journal of Nursing, 2011)
Background: Being a nursing mentor is not an entirely new concept in nursing. However, it is a new phenomenon in the nursing profession in Malaysia. The nursing administration and the senior nurses in Malaysia have claimed that they have started a mentorship program by having senior nurses shadow new graduate nurses for the past two to three years ago. With no study found in Malaysia investigating the lived experiences of mentors mentoring new registered nurses, it led the researcher to develop this research that explores the real life experiences of these senior Malaysian nurses who mentor neophyte nurses.Objectives: This research explores and describes the lived experiences of nurses mentoring neophyte or new registered nurses at one of the major hospital in the Malaysia Borneo and how such experiences influence their daily routine as a nurse and also as a mentor. The research will also attaches meaning to these experiences and identifies both positive and negative experiences as a mentor to neophyte.Methods: The experiences of nurses mentoring the neophyte in the clinical area were captured using a qualitative approach to research and further viewed through methods informed by phenomenology, which used interpretive and descriptive semi-structured interviews. Hermeneutic interpretive phenomenology was used in the focus to analyze interview transcript into textual expression of the mentors. Three main themes emerge from this study are being unprepared and challenged, perceptions of mentees, mentor hope and desire.Key words: nursing mentor, phenomenon, neophyte, Malaysia.